Magnetic surfaces of an l=4 stellarator in regard to helical coil angular size and method of conductor turn packing - Kotenko, V.G. (Вопросы атомной науки и техники, 2009)
Numerical studies were undertaken to elucidate the influence of the helical-coil finite angular size on l=4 stellarator
magnetic surface characteristics. The calculations are applied to the closed magnetic surface configuration removed
from the torus surface. The magnetic surface characteristics did not change significantly in comparison with ideal model
of the l=4 stellarator magnetic system. Виконано чисельне дослідження впливу скінченної кутової ширини гвинтових обмоток на властивості
магнітних поверхонь в 4-заходному стелараторі. Розрахунки торкаються конфігурації замкнутих магнітних
поверхонь, віддалених від поверхні тора. Властивості магнітних поверхонь в порівнянні з ідеальною моделлю 4-
заходного стеларатора суттєвих змін не зазнали. Проведено численное изучение влияния конечной угловой ширины винтовых обмоток на свойства магнитных
поверхностей в 4-заходном стеллараторе. Расчеты относятся к конфигурации замкнутых магнитных
поверхностей, удаленных от поверхности тора. Свойства магнитных поверхностей по сравнению с идеальной
моделью 4-заходного стелларатора существенно не изменились.